Maine’s Future Housing Needs: An MPR Interview with David Lakari - Lakari, David (Maine Policy Review, 1999)
Since 1994, David Lakari has been director and chair of the Maine State Housing Authority. The Maine State Housing Authority is an independent state agency and a 1.5 billion financial institution. Its mission is to help Maine’s low- and moderate-income citizens obtain and maintain decent, safe, and affordable housing and services suitable to their needs. In this interview, Lakari focuses on his concerns for the future, in particular, the need to find suitable housing options for one of Maine’s fastest-growing demographic groups—the middle-income elderly. While Maine has been doing a good job of building the capacity to house its wealthy and low-income elderly, without shifts in current development, middle-income “baby boomers” may find it difficult to obtain suitable housing as they age. Unfortunately, such projections come at a time when the federal government is reducing its commitment to affordable housing. Lakari discusses the implications of these factors and their potential effects on housing costs and homelessness.